Concentración de Lactato e influencia Metabólica Láctica en el Rendimiento Físico del Seleccionado de Triatlón de la Universidad del Quindío (2019)
Objective: To determine the concentration of lactate of the triathletes of a university of Quindío, in the first semester of the year 2017. Materials and methods: Descriptive, exploratory cross-sectional study. The maximal aerobic power test, Leger test, was applied to specify the maximum oxygen consumption. The concentration of lactate was determined in three moments: at rest, just after finishing the test and after 10 minutes of recovery, by the implementation of a team of Lactate Scout that allowed to determine the blood lactate by means of reflection photometry with reactive strips, In addition, a monitoring of the heart rate was carried out in the three moments, by means of pulsars marked POLAR and the anthropometric variables of mass, height and body mass index were determined. Descriptive and inferential statistics were performed, for the latter a repeated measure ANOVA was performed, using the SPSS Statistics software. Results: The concentration of lactate increased in the second time 891 times in men and 653 times in women, later it decreased 18 times in men and 27 times in women. Likewise, the heart rate increased 186 times in men and 132 times in women and decreased 41 times in both men and women. Conclusions: As a conclusion the women of this selected group had a higher lactate clearance capacity, in spite of having a lower performance than expected.